Savings behavior of private households in the United States and West Germany - Barbara Kauffmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
In the eighties, the relatively low ratio of U.S. national saving has been increasingly criticized. Many observers were concerned about its continued decline and the widening gap between the U.S. savings ratio and that of many other industrial countries. The savings rate decreased from an average of 7.9 p.c. in the period from 1973 to 1980 to an average of 3.2 p.c. between 1981 and 1987 (Table 1). In particular, the relatively low and declining U.S. propensity to save has at least partly been made responsible for the United States becoming a net importer of capital since 1982, and for their running a large current account deficit at the same time. This is viewed as violating the general rule that a relatively rich country should export capital rather than compete with developing countries for internationally mobile capital and thereby driving up borrowing costs for those countries. The behavior of countries like West Germany - having a relatively high propensity to save, exporting more capital than importing, and thus running large current account surpluses - is therefore considered more appropriate.
Keywords: 330